Adjunctive Chinese Herbal Medicine Treatment is Associated With an Improved Survival Rate in Patients With Cervical Cancer in Taiwan: A Matched Cohort Study. (November 2021) - Wang, Chieh; Lin, Kent Yu-Hsien; Wu, Mei-Yao; Lin, Cheng-Li; Lin, Jaung-Geng; Chang, Cherry Yin-Yi; Lin, Wu-Chou; Yen, Hung-Rong
Background: Cervical cancer is one of the most common cancers in Taiwan. Some patients take Chinese herbal medicine (CHM). However, very few current studies have ascertained the usage and efficacy of CHM in patients with cervical cancer. The aim of this study was to investigate the benefits of complementary CHM among patients with cervical cancer in Taiwan. Methods: We included the newly diagnosed cervical cancer patients who were registered in the Taiwanese Registry for Catastrophic Illness Patients Database between 2000 and 2010. The end of follow-up period was December 31, 2011. Patients who were less than 20 years old, had missing information for age, withdrew from the National Health Insurance (NHI) program during the follow-up period, or only received other TCM interventions such as acupuncture or tuina massage were excluded from our study. After performing 1:1 frequency matching by age and index date, we enrolled 7521 patients in both CHM and non-CHM user groups. A Cox regression model was used to compare the hazard ratios (HRs) of the risk of mortality. The Kaplan-Meier curve was used to compare the difference in survival time. Results: According to the Cox hazard ratio model mutually adjusted for CHM use, age, comorbidity, treatment, and chemotherapeutic agents used, we found that CHM users had a lower hazard ratio of mortality risk (adjusted HR = 0.29, 95%CI = 0.27-0.31). The survival probability was higher for patients in the CHM group. Bai-Hua-She-She-Cao ( Herba Oldenlandiae, synonym Herba Hedyotis diffusae) and Jia-Wei-Xiao-Yao-San were the most commonly prescribed single herb and Chinese herbal formula, respectively. Conclusions: Adjunctive CHM may have positive effects of reducing mortality rate and improving the survival probability for cervical cancer patients. Further evidence-based pharmacological investigations and clinical trials are warranted to confirm the findings in our study.